2020
DOI: 10.1080/17439760.2020.1738535
|View full text |Cite
|
Sign up to set email alerts
|

Mamma Mia – A randomized controlled trial of an internet intervention to enhance subjective well-being in perinatal women

Abstract: Subjective well-being (SWB) may buffer against psychosocial stressors such as the birth of a child. To assess the effectiveness of an unguided internet intervention ('Mamma Mia') on SWB among perinatal women, we investigated (1) whether the intervention group reported higher levels of SWB, (2) whether the effect of Mamma Mia changed over time (i.e. whether the intervention was more effective at some time points), (3) and potential moderators. In total, 1342 pregnant women were randomized to the Mamma Mia or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…However, adherence to the intervention was relatively low (only 32.5% women completed Be a Mom). This result is congruent with those found by previous research with web-based interventions applied to universal samples during the perinatal period [44,45] and could be explained by the hectic and challenging period women are experiencing, which leaves them with limited time for themselves. Additionally, Be a Mom is a fully self-guided intervention that was delivered to a low-risk sample with relatively good levels of overall mental health at baseline.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, adherence to the intervention was relatively low (only 32.5% women completed Be a Mom). This result is congruent with those found by previous research with web-based interventions applied to universal samples during the perinatal period [44,45] and could be explained by the hectic and challenging period women are experiencing, which leaves them with limited time for themselves. Additionally, Be a Mom is a fully self-guided intervention that was delivered to a low-risk sample with relatively good levels of overall mental health at baseline.…”
Section: Discussionsupporting
confidence: 92%
“…One study using an eHealth compassion-based intervention found that postpartum women in the intervention group showed an improvement in positive mental health compared to the control group [44], although the effects were small and only significant among participants with lower levels of positive mental health at baseline. Another study using an intervention based on positive psychology and metacognitive therapy only found a significant effect of the intervention with regard to emotional well-being [45]. The majority of web-based intervention studies in the perinatal period focus on the treatment or prevention of psychopathological symptoms using mostly high-risk samples [46].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, participants answered questions over a period of 2 weeks to ensure that any measured positive mood was a state. Moreover, although many studies have used the PANAS scale to measure individuals' positive emotional state (e.g., Craske et al, 2019;Haga et al, 2020;Plys and Desrichard, 2020), there are still some limitations. For example, individuals may be influenced by the need for social approval and, thus, exaggerate their positive mood.…”
Section: Study Limitations and Future Research Suggestionsmentioning
confidence: 99%
“…More specifically, positive emotions also appear to broaden one's thought-action repertoires and facilitate behavioral flexibility and build personal resources, such as social relationships and resilience (18)(19)(20). Considering these benefits and the call for prioritization of research focused on positive mental health (21), increasing studies have focused on directly addressing positive mental health as an intervention outcome [e.g., (22,23)], including in the perinatal period (10,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Although still limited and very recent, there is preliminary evidence of web-based cognitive behavioral therapy (CBT) interventions as well as compassionate and acceptance-based approaches in enhancing positive mental health in perinatal samples (10,24). This is the case of Be a Mom, a CBT unguided web-based intervention, which was recently found to be effective in improving positive mental health among low-risk postpartum women (25).…”
Section: Introductionmentioning
confidence: 99%